STRATEGI PENGELOLAAN KELAS PEMBELAJARAN BAHASA ARAB - Dian Ekawati (An Nabighoh Jurnal Pendidikan Dan Pembelajaran Bahasa Arab, 2018)
Classroom management means the effort to plan, organize, direct, coordinate, and control the learning groups undertaken by the teacher in search of learning objectives. The activity of the classroom management is aimed to create a stable and comfortable classroom atmosphere and condition so that teaching and learning activity can run effectively and effciently. The purpose of classroom management is to create good clasroom situations and conditions, eliminate barriers in teaching and learning activities, provide learning activities, foster and guide learners asper their social, economic, and cultural background. The approach of classroom management is the power approach, the teaching approach, the grup work approach, the electronics approach and pluralistic approach. The techniques of classroom management are approaching techniques, humor and appeals for student with problems.